HUBUNGAN POLA ASUH IBU DENGAN STATUS GIZI BALITA DI DESA TEGALJADI WILAYAH KERJA PUSKESMAS MARGA II TABANAN TAHUN 2022 - Desak Gede Yenny Apriani (JURNAL MEDIKA USADA, 2023)
Background : Nutritional problems in toddlers are diseorders of the health and welfare of toddlers, due to imbalance between intake and the body’s need for food and the efect of interaction of infectious diseases. Based on a preliminary study at Puskesmas Marga II, the total population of toddlers in Tegaljadi Village are 151 people and base on interviews with 10 respondents, 5 of them have toddlers with malnutrition status. Objective : To determine the relationship of mother parenting patterns with toddler’s nutritional status. Method : This study using descriptive correlation design and cross sectional approach. The sampling technique using purposive sampling with a total sample of 110 people. Data collection are done by giving questonnaires to respondents and measuring the weight of toddlers. The data was analyzed using the Spearman Rank test to see the significance of statistical calculations using a significant limit if p< 0,05. Result : The results of this study of respondents who have a good parenting patterns of 78.2% and 21.8% of adequate parenting patterns, while 1.8% of respondents with malnutrition status, 20.9% of adequate nutrition, 75.5% well-nourished, over nutrition as much as 1.8%. Conclusion : There is a significant relationship between mother parenting patterns and toddler’s nutritional status. Keywords : Toddlers, parenting pattern, nutritional status.